(untitled) (International Journal of Engineering Management Science, 2025)
Biomass briquettes are an eco-friendly and cost-effective alternative to fossil fuels, offering a sustainable solution to meet industrial and domestic energy needs. This project focuses on the production and evaluation of two distinct biomass briquette compositions: (1) Coconut Shell (60%), Sawdust (30%), and Starch (10%), and (2) Carbonized Coconut Shell (70%), Carbonized Bamboo Dust (20%), and Molasses (10%). The selected materials are abundant, renewable, and capable of delivering significant calorific values while reducing environmental pollution. The research highlights the steps involved in the carbonization process, including feedstock collection, drying, pyrolysis, and briquette formation. The resulting briquettes were evaluated for key properties such as calorific value, ash content, moisture retention, and combustion efficiency. Experimental results demonstrate that carbonized bio-waste briquettes provide a high-energy yield while minimizing environmental impact. Additionally, the process contributes to waste management by reducing landfill accumulation and greenhouse gas emissions. The project explores the complete briquetting process, including material preparation, carbonization (where applicable), mixing, pressing, and drying. Both compositions were analysed for calorific value, combustion efficiency, ash content, and emissions to identify their suitability for various industrial applications. Composition 1 provides a moderate calorific value ( 18,010 kJ/kg), making it ideal for applications such as brick kilns, textile dyeing units, and small-scale food processing. Composition 2 delivers a higher calorific value ( 26,100 kJ/kg) and is suited for high-energy applications like cement kilns, metallurgical industries, and power plants. Cost analysis, energy efficiency (kJ/₹), and environmental benefits were also evaluated to determine the economic and sustainable advantages of these briquettes. The results highlight the potential of biomass briquettes as a reliable and renewable energy source, contributing to reduced dependency on coal and other non-renewable fuels. This study reinforces the role of bio-waste utilization in achieving energy sustainability and environmental conservation.